2005
DOI: 10.1097/01.mcg.0000152780.76524.a9
|View full text |Cite
|
Sign up to set email alerts
|

Motility Abnormalities in Esophageal Body in GERD

Abstract: Esophageal manometric abnormalities should be considered cautiously before considering a motor disorder as a consequence of abnormal reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…This finding was compatible with the other studies, one of which was performed by Rios et al (22) and demonstrated that hypotensive LES with or without esophageal motor abnormalities was found in more than one-third of GERD patients. They also comment that IEM was the disorder most strongly related to reflux.…”
Section: Discussionsupporting
confidence: 82%
“…This finding was compatible with the other studies, one of which was performed by Rios et al (22) and demonstrated that hypotensive LES with or without esophageal motor abnormalities was found in more than one-third of GERD patients. They also comment that IEM was the disorder most strongly related to reflux.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, pH, bile acid and trypsin levels in GERD have been studied as biomarkers for chronic allograft dysfunction (3). GERD is also associated with esophageal motor disorders (EMD), although it is not clear if GERD is the cause or the consequence of the esophageal motility impairment (4). Although GERD has been extensively studied as a factor associated with LTx rejection, there are some gaps with regard to the potential contribution to the abnormal motility of the esophagus.…”
Section: Introductionmentioning
confidence: 99%